Prognosis End-Time: Madness and Prophecy in Melancholia and Take Shelter (Altre Modernità, 2013)
This paper discusses two films released in 2011, Lars Von Trier's Melancholia and Jeff Nichols Take Shelter in the context of the history of dominant conceptions of madness as laid out in Foucault's History of Madness. I argue that these films allegorise protagonists' experiences of depression and schizophrenia in order to critique the present moment in North America as well as to restore a poetic link between madness, prophecy and apocalypse in the popular imagination.
Keywords: Madness; Foucault; Apocalypse; Film; von Trier; Jeff Nichols